Pipeline or Pipe Dream: Building a Scaled Automated Metadata Creation and Ingest Workflow Using Web Scraping Tools - Matthew Krc and Anna Oates Schlaack (Code4Lib Journal)
Since 2004, the FRASER Digital Library has provided free access to publications and archival collections related to the history of economics, finance, banking, and the Federal Reserve System. The agile web development team that supports FRASER’s digital asset management system embarked on an initiative to automate collecting documents and metadata from US governmental sources across the web. These sources present their content on web pages but do not serve the metadata and document links via an API or other semantic web technologies, making automation a unique challenge. Using a combination of third-party software, lightweight cloud services, and custom Python code, the FRASER Recurring Downloads project transformed what was previously a labor-intensive daily process into a metadata creation and ingest pipeline that requires minimal human intervention or quality control. This article will provide an overview of the software and services used for the Recurring Downloads pipeline, as well as some of the struggles that the team encountered during the design and build process, and current use of the final product. The project required a more detailed plan than was designed and documented. The fully manual process was not intended to be automated when established, which introduced inherent complexity in creating the pipeline. A more comprehensive plan could have made the iterative development process easier by having a defined data model, and documentation of—and strategy for—edge cases. Further initial analysis of the cloud services used would have defined the limitations of those services, and workarounds could have been accounted for in the project plan. While the labor-intensive manual workflow has been reduced significantly, the required skill sets to efficiently maintain the automated workflow present a sustainability challenge of task distribution between librarians and developers. This article will detail the challenges and limitations of transitioning and standardizing recurring web scraping across more than 50 sources to a semi-automated workflow and potential future improvements to the pipeline.